PENGARUH PROMOSI TENAGA KESEHATAN TERHADAP PENINGKATAN PEMBERIAN IMUNISASI CAMPAK RUBELLA DI PUSKEMAS BANDAR KHALIPAH TAHUN 2019 - Mestika Rija Helti; Suriani; Zakiah (Jurnal Ilmiah Kebidanan Imelda, 2019)
Measles and rubella can have a negative impact on children's health in Indonesia, so the government has implemented an MR vaccination campaign (MMR VIS - Indonesia, 2012). The MR (Measles Rubella) vaccine provides benefits such as protecting children from disability and death due to complications of pneumonia, diarrhea , brain damage, deafness, blindness and congenital heart disease. There were 83 confirmed cases of CRS in 2015-2016 of which 77% suffered from heart defects, 67.5% suffered from cataracts and 47% suffered from deafness (Ditjen P2P, 2016). The research objective was the Effect of Promotion of Health Workers on the Improvement of Rubella Measles Immunization at the Bandar Khalipah Public Health Center in 2019. This type of research is descriptive analytic with a cross sectional approach with a sample size of 18, it is recommended to carry out promotions. The sampling technique is purposive sampling technique. The research instrument uses leaflet sheets. Univariate analysis using Microsoft Excel. The results showed that the total coverage of rubella measles immunization prior to promotion at the Bandar khalipah health center 2019 was 340 (7.8%) in the "decreased" category and after promotion the total coverage of rubella measles immunization at the Bandar khalipah puskesmas was 367 (8, 6%) are in the “increasing” category. So that there is an effect of promotion of health workers on increasing the provision of rubella measles immunization at the Bandar khalipah public health center in 2019. Conclusion in this study there is an effect of promotion of health workers on increasing rubella measles immunization, so that health workers can use promotion as an effort to support government programs, coverage of immunization rubella measles 95%.